Application of two-dimensional leaf-shaped zeolitic imidazolate framework (2D ZIF-L) as arsenite adsorbent: Kinetic, isotherm and mechanism - Nasir, A.M. (Elsevier B.V., 2018)
Two-dimensional leaf-shaped zeolitic imidazolate framework (ZIF-L) was synthesized in aqueous solution by using zinc salt and 2-methylimidazole (2-MeIM) at room temperature. The synthesized ZIF-L shows unique two-dimensional (2-D) leaf-like crystal morphology using field emission scanning electron microscope. The crystalline structure and total surface area of ZIF-L was indicated by X-ray diffraction, thermogravimetric analysis and BrunauerâEmmettâTeller analysis. The experimental data of adsorption of arsenite by ZIF-L were well fitted by two-site- pseudo-second-order kinetic model. The adsorption isotherms were well described by Freundlich isotherm model. The synthesized ZIF-L possess maximum uptake of arsenite was 43.74 mg/g at pH 10.0 at the room temperature (25.0 Â± 1 Â°C) which is relatively higher than other class of metal-organic framework. Zeta potential, fourier transform infrared, and scanning electronic microscope combined with X-ray energy dispersive spectrometer concluded that adsorption mechanism of arsenite on ZIF-L was occurred based on electrostatic interaction between arsenite ions and surface charge of ZIF-L, also substitution of hydroxyl group by arsenite to form inner-sphere complex. Since the development of ZIF-L through aqueous media was rapid, simple and eliminated the heating process, ZIF-L can be regarded as a promising adsorbent and low-cost adsorbent for the removal of arsenite. Â© 2017 Elsevier B.V.